Communication sciences and disorders : an evidence-based approach - Justice, Laura M., 1968-; Redle, Erin E. (Boston Pearson, 2014)
'Introduces students to the field through clinicians, patients, and families. Rich with examples, the first part covers foundational concepts of development, anatomy, physiology, augmentative communication and complex communication. Following these foundations, the second part highlights inherited and acquired disorders affecting children and older adults. A new chapter features multicultural topics, while an expanded chapter delves into advancements in assessment and intervention. Strong themes of literacy weave throughout. Expanded cased keep student interest with evaluation and treatment sections.' --
Pt. I. Foundations of Communication Sciences and Disorders -- Ch. 1. Fundamentals of Communication Science and Disorders -- Ch. 2. An Overview of Communication Development -- Ch. 3. Anatomical and Physiological Bases of Communication and Communication Disorders -- Ch. 4. Augmentative and Alternative Communication -- Ch. 5. Communication Disorders in a Multicultural World -- Pt. II. Communication Disorders Across the Life Span -- Ch. 6. Communication Assessment and Intervention: Evidence-Based Practices Ch. 7. Language Disorders in Early and Later Childhood -- Ch. 8. Adult Language Disorders and Cognitive-Based Dysfunctions -- Ch. 9. Speech Sound Disorders in Children -- Ch. 10. Fluency Disorders -- Ch. 11. Voice Disorders -- Ch. 12. Motor Speech Disorders -- Ch. 13. Pediatric Hearing Loss -- Ch. 14. Hearing Loss in Adults -- Ch. 15. Feeding and Swallowing Disorders.
Previously published as Communication sciences and disorders : a contemporary perspective, 2010.
Includes bibliographical references and indexes.
Keywords: Communicative disorders; Speech Disorders